The Sulphur Dioxide (SO2) Gas and the Total Suspended Particulate Contents of the Ambient Air of Kupang City: Case Report - Welem A. Faot; Suwari; Sherlly Ledoh (Journal of Applied Chemical Science, 2012)
A research has been done to find out the concentration of sulfur dioxide gas (SO2) and the total suspended particulate (TSP), as well as correlation between the amount of vehicle and the concentration of SO2 and TSP ambient air in subdistrict Oebobo of Kupang City. The measuring of SO2 using pararosaniline method, while the TSP was measured by using digital particle concentration meter. The results showed that the highest concentration of SO2 was found on Nangka Street (in the afternoon) that was 148.05 μg/Nm3 and the lowest was on Palapa Street (in the afternoon) that was 106.55 μg/Nm3. The highest concentration of TSP was recorded from the Amabi Street (in the morning) which was 49.50 μg/Nm3 and the lowest concentration was recorded from the Palapa Street (in the afternoon) was 17.95 μg/Nm3. There is a correlation between the amount of vehicle and concentration of SO2, and correlation between the amount of vehicle and concentration of TSP.